Analisis Likuiditas Dan Pertumbuhan Penjualan Terhadap Nilai Perusahaan Pada Perusahaan Subsektor Infrastruktur Transportasi Di Bursa Efek Indonesia Periode 2017-2023 - Raida Dzaqiatul Haqimah; Diah Yudhawati; Rahmat Mulyana Dali (CV. ITTC INDONESIA, 2024)
The purpose of this study is to determine the effect of liquidity and sales growth on company value in transportation infrastructure sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2023 period. The population in this study consists of 9 transportation infrastructure sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2023 period. The sampling technique uses the purpose sampling method. The data sources obtained in this study are secondary data in the form of company financial reports. The types of data used in this study are quantitative data with descriptive analysis, panel data regression, classical assumption tests, multiple linear regression tests, hypothesis tests and determination coefficient tests. The selected model is the random effect model (REM). The results of the study show that liquidity (X1) partially has no significant effect on company value, sales growth (X2) partially has a significant effect on company value. and simultaneous data analysis shows that liquidity (X1) and sales growth (X2) have a significant effect on company value.